Positive Impact Analysis of Kasti Traditional Games on Social Interactions of Elementary School - Dewi Anggraini; Aan Widiyono; Abdullah Efendi (Journal Of Sport Education (JOPE), 2023)
The aim of this research is to determine the positive impact of the traditional game of kasti on the social interactions of students at SDN 4 Kedungcino. The type of research used is qualitative research using observation, interviews and documentation methods. The research sources consisted of sports teachers and student representatives from SDN 4 Kedungcino. Checking the validity of data with credibility, transferability, dependability and confirmability. Data analysis techniques use data reduction, data presentation and verification conclusions. Based on the results of the researcher's analysis, it can be said that the traditional game of Kasti has a positive impact on students, therefore the traditional game of Kasti must be preserved and cultivated among children today.